A survey of RFID authentication protocols - Yousuf, Y.; Potdar, Vidyasagar (IEEE Computer Society, 2008)
RFID are small wireless devices which can be used for identification of objects and humans as well. Their acceptance has grown in past years and is expected to grow further. Due to reduction in cost of production RFID devices are being deployed in large numbers in supply chains (by Wal-Mart, etc.) In this paper we provide a comprehensive survey of various RFID authentication protocols proposed in the literature and classify them in different categories. We then study two main RFID authentication protocols namely LMAP and M2MAP